Pendampingan Pembelajaran Mufradat bagi Siswa Kelas X MA Nurudz Dholam Kedungdung Sampang - Moh. Hasyim Asy’ari (LP2M Institut Agama Islam Nazhatut Thullab Sampang, Indonesia, 2026)
Learning a foreign language requires vocabulary mastery. In Arabic language learning at MA Nurudz Dholam in grade X, when the teacher asked about vocabulary, most of the students did not understand the vocabulary. Therefore, special assistance was needed to overcome this problem. The purpose of this community serXce was to proXde assistance to teachers and students. The research used a qualitative approach to obtain the necessary data in the field. The results of the assistance included the use of images, direct methods, and chain word guessing games in vocabulary learning. After the assistance, grade X students' interest in learning vocabulary increased.